0110 Within-subject Consistency Of Increased Interleukin-6 Levels In Response To Combined Sleep Restriction And Circadian Misalignment In Humans. (12th April 2019) - Blumenstein, Alivia B; Sprecher, Kate; Hay-Arthur, Emily; Schreiber, Austin J; Burke, Tina M; Depner, Christopher M; Dorrestein, Pieter C; Fleshner, Monika; Knight, Rob; Lowry, Christopher A; Turek, Fred W; Vitaterna, Martha H; et al.
Abstract: Introduction: Interleukin (IL)-6 is a known mediator of inflammation and has been reported to increase after sleep restriction, in some but not all studies, and during circadian misalignment with 8h sleep opportunities. However, the effects of combined sleep restriction and circadian misalignment on IL-6 and the within-subject consistency of this response is unknown. Methods: Twenty healthy adults (8 female), age 25.65(±4.2), BMI 21.97 (±2.2) kg/m 2 (±SD), completed two 18-day protocols consisting of 2 weeks of self-selected 8h sleep schedules at home followed by a 4-day laboratory visit. During the 4-day visit, participants were given an 8h sleep opportunity on night 1, 3h opportunity on night 2, and 3h opportunities during mornings 3 and 4. Ten blood draws occurred during each visit: baseline after the first 8hr sleep opportunity, a second draw after the first 3hr sleep opportunity, and draws every 6hr thereafter. IL-6 concentration was assessed using a multiplex immunoassay; raw concentration values were log10 transformed. Change in IL-6 concentration over time was assessed using mixed model ANOVA and t -tests were used to determine differences from baseline at each time point. Intra-class correlation coefficients (ICC), derived from mixed model ANOVAs, were used to quantify the stability of individual differences in IL-6 levels at baseline and during combined sleep restriction and circadian misalignment. Results: Average IL-6 concentration was increased during combined sleep restriction and circadian misalignment compared to baseline at all time points during visit 1 ( p< 0.025 adjusted for multiple comparisons) and time points 3-10 during visit 2 ( p< 0.025 adjusted for multiple comparisons). IL-6 concentration showed almost perfect trait-like stability (ICC 0.85) across visits at baseline and showed moderate consistency (ICC 0.44) across visits during combined sleep restriction and circadian misalignment (average of samples 2-10). Conclusion: Combined sleep restriction and circadian misalignment produces a significant and moderately stable inflammatory response. The implications and nature of this response remains unclear and further research is required. Support (If Any): Office of Naval Research MURI (N00014-15-1-2809); NIH/NCATS (UL1TR002535); Undergraduate Research Opportunities Grant University of Colorado Boulder.